The MDM2 promoter polymorphism SNP309T→G and the risk of uterine leiomyosarcoma, colorectal cancer, and squamous cell carcinoma of the head and neck. Issue 9 (1st September 2005) - Alhopuro, P; Ylisaukko-oja, S K; Koskinen, W J; Bono, P; Arola, J; Järvinen, H J; Mecklin, J-P; Atula, T; Kontio, R; Mäkitie, A A; Suominen, S; Leivo, I; et al.
Abstract : Background: MDM2 acts as a principal regulator of the tumour suppressor p53 by targeting its destruction through the ubiquitin pathway. A polymorphism in the MDM2 promoter (SNP309) was recently identified. SNP309 was shown to result, via Sp1, in higher levels of MDM2 RNA and protein, and subsequent attenuation of the p53 pathway. Furthermore, SNP309 was proposed to be associated with accelerated soft tissue sarcoma formation in both hereditary (Li-Fraumeni) and sporadic cases in humans. Methods: We evaluated the possible contribution of SNP309 to three tumour types known to be linked with the MDM2/p53 pathway, using genomic sequencing or restriction fragment length polymorphism as screening methods. Three separate Finnish tumour materials (population based sets of 68 patients with early onset uterine leiomyosarcomas and 1042 patients with colorectal cancer, and a series of 162 patients with squamous cell carcinoma of the head and neck) and a set of 185 healthy Finnish controls were analysed for SNP309. Results: Frequencies of SNP309 were similar in all four cohorts. In the colorectal cancer series, SNP309 was somewhat more frequent in women and in patients with microsatellite stable tumours. Female SNP309 carriers were diagnosed with colorectal cancer approximately 2.7 years earlier than those carrying the wild type gene. However, no statistically significant association of SNP309 with patients' age at disease onset or to any other clinicopathological parameter was found in these three tumour materials. Conclusion: SNP309 had no significant contribution to tumour formation in our materials. Possible associations of SNP309 with microsatellite stable colorectal cancer and with earlier disease onset in female carriers need to be examined in subsequent studies.